Teachers' efforts to instill the values ​​of Islamic religious education in children with autism at SDLB Negri Rantauprapat: Teachers' efforts to instill the values ​​of Islamic religious education in children with autism at SDLB Negri Rantauprapat - Syahputra, Agus; megawai, betti; Syawaluddin, Fauziahmad (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to determine teachers' efforts to instill Islamic religious education values ​​in children with autism at SDLB Rantauprapat, both through tests and non-tests. The population in this research were children with autism at SDLB Rantauprapat. This research was conducted at SDLB Rantauprapat with the aim of finding out 1) The teacher's work program in instilling Islamic religious values ​​in students with autism at SDLB Rantauprapat. 2) Obstacles Encountered by Teachers in Instilling Islamic Values ​​in Students with Autism at SDLB Rantauprapat. 3) Solutions implemented by teachers in instilling Islamic religious values ​​in students with autism at SDLB Rantauprapat. This research uses descriptive qualitative research methods. The data collection techniques used in this research are observation, interviews and documentation. The observation method is carried out by observing the school and the school environment related to the teacher's efforts in instilling Islamic religious education values ​​in children with autism. The interview method used was a planned-unstructured interview. The final method is documentation in the form of documents, school files, photos and other data. Then the technique for analyzing data in this research uses triangulation. From the explanation above, it can be concluded 1. The efforts of parents and teachers to instill Islamic religious values ​​in students with autism are carried out well and optimally. Parents and teachers both use habituation methods, example and advice in instilling Islamic religious values, including the values ​​of piety, gratitude and patience. In instilling the value of piety, parents try to provide good religious knowledge for their children so that they can know their God.